HUBUNGAN ASPEK SOSIOLOGI PENGARANG DENGAN UNSUR INTRINSIK DALAM NOVEL NIJUUSHI NO HITOMI - Miuri Legi Lestari; Anisa Arianingsih; Fenny Febrianty (Janaru Saja Jurnal Program Studi Sastra Jepang, 2017)
This study discusses the relationship between the author's sociological aspects with intrinsic elements contained in the novel Nijuushi No Hitomi by Sakae Tsuboi. The purpose of this research is to know how the relationship between novel Nijuushi No Hitomi and sociology aspect Sakae Tsuboi as the author. The object of this research is a quote in the form of narrative and dialogue in the novel that is considered to have a relationship with the author's sociological aspects. The research method used is descriptive method of analysis based on the theory of sociology author by Wellek & Warren (1994). The results of this study indicate a relationship between the author's sociological aspects and intrinsic elements in the novel.